Stany Zjednoczone jako ekonomiczny partner państw Azji - Jankowiak, Anna (USA as an Economic Partner for Asian Countries, 2008)
US are doing business all over the world, trading with every major national economy. The situation in which Europe is the most significant trading partner for America, is now changing. The Asian region is playing more and more important role in the circulation between US and the rest of the world. We can assume with high probability that in the 21st century, Asia will become a center of American interest. Trading between US and Asia is significant for both sides. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 88-97